Neutrophil-to-Lymphocyte Ratio, Mediterranean Diet, and Bone Health in Coeliac Disease Patients: A Pilot Study. (20th June 2019) - Palmacci, Francesca; Toti, Elisabetta; Raguzzini, Anna; Catasta, Giovina; Aiello, Paola; Peluso, Ilaria; Biava, Mariangela; Palmery, Maura
Abstract : Neutrophil-to-lymphocyte ratio (NLR) has been proposed as a bone loss index in postmenopausal women and as a marker of inflammation in coeliac patients. The aims of this work were to evaluate the effect of gluten-free diet (GFD) on NLR retrospectively and study the relationship between NLR and Mediterranean diet adherence and selected food groups (fruits, vegetables, red meat, potatoes, and unrefined and refined cereals). Adult individuals (n = 50 ), who had been on a strict GFD by at least 6 months, were recruited. The degree of adherence to the Mediterranean diet was calculated with two different scores: the Mediterranean Diet Score (MDS-14), assessed through the validated 14-item questionnaire of the PREDIMED study, and the MEDScore (Score-55) proposed by Panagiotakos. The latter includes the consumption of unrefined cereals (UC). High percentages of osteopenia and osteoporosis were found within the recruited subjects, who furnished the reports of bone mineral density (BMD), in particular in postmenopausal (Post-M) women. Recent NLR was higher in subjects with osteoporosis compared to osteopenia and normal BMD. However, retrospective analysis showed both increase and decrease in NLR after GFD, with no significant differences between Marsh grade, anemia, and BMD status. Moreover, premenopausal previous pregnancy (Pre-MPP) and Post-M had higher NLR at diagnosis compared to Men and premenopausal (Pre-M), but higher differences were observed in recent NLR between Pre-MPP and Men only. Chocolate consumption was associated with lower recent NLR, whereas the latter was correlated with Score-55, but not with MDS-14. Moreover, refined cereal consumption was correlated with recent NLR. Although large prospective studies are needed in order to clarify the relationship between UC and NLR in coeliac patients, in this pilot study, we have investigated for the first time the relationship between NLR, dietary habit, and osteoporosis in coeliac disease.